Tradução e adaptação cultural da COVID stress scales no Brasil - Pellegrini, Andréa Regina (2023)
The Coronavirus Disease -COVID-19- pandemic is currently one of the greatest public health emergencies the international community has been facing. In addition to concerns on physical health, that disease also raises concerns on mental health, since psychological suffering can be experienced by the population and health professionals, directly impacting their quality of life. The intensification of fear, anger, stress, insecurity and frustration are associated to a higher risk of psychiatric disorders devepment. In that context, the availability of a stress measurement instrument related to COVID-19 and Mental Health is of great relevance. The COVID Stress Scales (CSS) is an instrument that measures the stress resulting from COVID-19. The CSS was developed in Canada and the United States and to evidence its reliability as well as its validity. The objective of this study was to translate and to adapt the CSS culturally to Brazil. This methodological study respected the steps recommended in the literature. The project was approved by the Research Ethics Committee of the Federal University of São Carlos. The accomplished phases were: translation performed by two independent and bilingual translators producing two versions of the instrument; synthesis of the translations carried out by the researchers together the translators to produce a consensuous version; instrument back-translated into the original language by another translator; review carried out by a Committee of specialists composed of 07 judges. From the thirty-six items in the CSS consensuous version, thirty-two had a CVI=1, which were considered equivalent and maintained in the pre-final version; four of then presented CVI=0,86 not requiring any modification, one item referring to the scale score and one item on the explanatory note about compulsive behavior presented CVI=0,71 and they were modified as suggested by the specialists. The pre-test was performed by 40 participants, who were 47,53 (± 13,99) years old in average, ranging from 19 to 78 years old. Most of them were female (70%) and married or in a stable union (40%). The average number of schooling years was 13,90 and their average income was 4.096,77 reais. Cronbach's alpha ranged from 0,81 to 0,95. Like this study, other countries also reported a coefficient similar to the original CSS, confirming satisfactory values of internal consistency in all domains of the instrument. In the present study, the CSS is named COVID-19 Stress Scale and its continuity is essencial for its validation as well as its use in future researches.